POLITICAL ECONOMY OF AFRICA: A COMPARATIVE ANALYSIS OF NIGERIA AND SOUTH AFRICA - OKOLO, Philips O.; EFEBEH, Vincent Eseoghene; BOUBAI, Joseph Jackson (EBSU Journal of Social Sciences and Humanities, 2024)
The paper analyzes the political economy of Africa in view of Nigeria and South Africa. The political economy approach was adopted and explore predominately the qualitative methods of data collection and adopted content analysis. It unraveled that Africa in relation to other continents in the world is quite backward and underdeveloped, and Nigeria and South Africa are crystal-clear indications of the ugly fact. However, looking inward, political economy of countries like South Africa is quite advanced in comparison with countries like Nigeria in terms of political and economic development. This is apparent when comparing the GDP trend of both countries where Nigerian GDP per capita is far below that of South. It therefore implies that the living standard (both economically and politically) is much better in South Africa in comparison with that of Nigeria. It therefore suggested among others the urgent need for both governments to have socio-political and economic policies directed at reducing poverty level, which include providing employment opportunities, human capital development.